2015
DOI: 10.25100/cm.v46i4.1887
|View full text |Cite
|
Sign up to set email alerts
|

La prevención de la preeclampsia: un estudio de casos y controles anidado en una cohorte

Abstract: Background: Preeclampsia is the main complication of pregnancy in developing countries. Calcium starting at 14 weeks of pregnancy is indicated to prevent the disease. Recent advances in prevention of preeclampsia endorse the addition of conjugated linoleic acid. Objective: To estimate the protective effect from calcium alone, compared to calcium plus conjugated linoleic acid in nulliparous women at risk of preeclampsia. Methods: A case-control design nested in the cohort of nulliparous women attending anten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Herse et al reported that the EETs including 5,6-EET, 14,15-EET, and the dihydroxyeicosatrienoic acids, were elevated in the preeclamptic women due to the up-regulated expression of the CYP subfamily 2J polypeptide 2 (CYP2J2) [34]. More importantly, the supplement of linoleic acid during pregnancy has been reported to be bene cial to the prevention and management of PE [35].…”
Section: Discussionmentioning
confidence: 99%
“…Herse et al reported that the EETs including 5,6-EET, 14,15-EET, and the dihydroxyeicosatrienoic acids, were elevated in the preeclamptic women due to the up-regulated expression of the CYP subfamily 2J polypeptide 2 (CYP2J2) [34]. More importantly, the supplement of linoleic acid during pregnancy has been reported to be bene cial to the prevention and management of PE [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Levine et al 23 in a prospective study in American population showed that calcium supplementation during pregnancy did not prevent preeclampsia in healthy nulliparous women. Recently Alzate et al 24 reported that calcium supplementation during pregnancy did not have preventive effects on preeclampsia. But calcium plus conjugated linoleic acid provided to adolescents was observed to have preventive effect on preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Alzate et al 1 http://www.ncbi.nlm.nih.gov/pmc/articles/PMC4732504/ , conducted a nested case-control study to (quote) "estimate the protective effect from calcium [supplement] alone [CC], compared to calcium plus conjugated linoleic acid [CC+CLA] in nulliparous women at risk of preeclampsia". Based on a crude analysis of the data in Table 3 1 , they concluded that neither CC nor CC+CLA reduced the risk of preeclampsia in the whole sample, but that CC+CLA significantly decreased risk among women 13-18 years old. A quick look analysis of the data in this table shows this conclusion is mostly based on the fact that none of the cases in 13-18 year old women was treated with CC+CLA.…”
mentioning
confidence: 99%